Spent coffee ground biochar for the adsorption of phenolic compounds: influence of pyrolysis conditions and hydrolysate concentration - Leticia Vicente Moreno; Mariana de Oliveira Bérgamo; Sophie Anna Grünwald; Syed Sikandar Shah; Ernesto Antonio Urquieta-Gonzalez; Kelly Johana Dussán (Environmental Science and Pollution Research, 2026)
This study investigates the use of biochar produced from spent coffee grounds (SCG) as an adsorbent for phenolic compounds found in sugarcane bagasse hydrolysates. SCG is an abundant sustainable and low-cost agro-industrial residue, which was evaluated as potential adsorbent for removing fermentation inhibitors commonly found in lignocellulosic hydrolysates. Biochar samples E1 to E6 were produced via pyrolysis under nitrogen atmosphere including a final thermal treatment under air at 300 °C, varying the applied temperature and pyrolizer inclination. The biochars were characterized using N 2 adsorption/desorption measurements, thermogravimetric analysis (TGA), and Fourier-transform infrared spectroscopy (FTIR). Adsorption experiments were conducted using hydrolysates at five concentration levels (1.0- to 3.0-fold), and the biochar were tested at different contact times. The results showed that both pyrolysis temperature and pyrolizer inclination significantly influenced the adsorption performance. Biochars E5 and E6, produced under the central point condition (500 °C and 4.4°), exhibited the highest phenolic compound removal, reaching an average removal efficiency of 49.5% in the 3.0 × concentrated hydrolysate. Moreover, post-pyrolysis calcination markedly improved capacity and early time adsorption using non-concentrated hydrolysate. The Temkin isotherm model was the best to fit the equilibrium data, while kinetic analyses showed strong correlations with the pseudo-first-order and Elovich models, particularly at higher hydrolysate concentrations. These findings demonstrate that SCG-derived biochar were obtained with favorable physicochemical characteristics making it effective for the adsorption of phenolic compounds. Overall, this approach offers a promising strategy for hydrolysate detoxification and waste valorization, contributing to cleaner and more sustainable biotechnological processes.